Periodical literature and online whiteboard as alternatives to textbook - Nur Anneliza Abd Latip; Hanita Hanim Ismail; Harwati Hashim; Wardatul Akmam Din (Springer, 2025)
Textbook role in English language education is imperative in providing curriculum structure, standardising instruction, and maintaining the quality of teaching. Often it is an efficient material for teachers as it is readily available and reliable. Nonetheless, the one-size-fits-all material may not reflect real life language outcome. In reading section of textbook, the passages are simplified, adapted and inauthentic. In a class geared towards high stake reading examination, textbook is needed as it is mirroring language test format, making it a mock test situation. This research exposed students in tackling reading class to texts from periodical literature and explored them using an online whiteboard. The research is not striving to replace textbook, rather put forwards materials that provide learners with opportunity to have an active role in directing their own cognitive resources in reading. The study aims to investigate whether the intervention of using these materials have an effect towards reading achievement. A quasi-experimental design was applied to see quantitative evidence of reading marks. The participants were pre-university students studying at Universiti Malaysia Sabah, one of the public institutions in Malaysia. The findings show that students who are using the periodical literature and online whiteboard revealed significant changes and higher marks of reading achievement compared to the group of students who are only using textbook. The study is hoped to supplement reading class with relevant materials of authentic text and current technology.